Progress and future of biodiesel synthesis: Advancements in oil extraction and conversion technologies. (15th February 2019) - Karmakar, Bisheswar; Halder, Gopinath
Highlights: Feedstocks have been categorized according to their generation or type. Various classic and modern oil extraction techniques are illustrated. Classic and conventional biodiesel production strategies have been discussed. Detailed discussion of supercritical and superheated transesterification is presented. Intensification processes for supercritical transesterification have been reviewed. Abstract: Biodiesel has gained the forefront of our focus on renewable transportation fuels. This article provides a comprehensive review on the sources used as feedstock and their classification based on generation or type (edible, non-edible, waste resources and animal fats) along with a variety of classical and modern oil extraction techniques. The technical aspects of the various biodiesel production methods currently implemented to the best of our knowledge are discussed here, which include in-situ biodiesel production, both catalysed (homogeneous and heterogeneous systems) and uncatalysed classical production approaches, with emphasis on how each of these approaches are affected by their reaction parameters. The review also highlights the observed drawbacks of each process with a view to assessing the implementation of supercritical and superheated technologies as an alternative, economically feasible advancement. Supercritical process (SCP) has shown great prospect in the obtainment of high quality biodiesel from a wide range of high to low grade feedstock with minimal impacts on the presence of water or FFAs (free fatty acids). From available literature it is shown that these do not affect the process significantly, and various other supercritical fluids such as methyl acetate, tert -butyl methyl ether (MTBE) and dimethyl carbonate can also be used to avoid glycerol formation. The process however, suffers from high initial implementation cost being the most prominent drawback, among others like thermal degradation of the fuel. Another promising technique, the superheated vapour technology (SHV) has emerged as an alternative, with limited literature proving the superiority of either of these processes to be inconclusive. In future works, researchers need to look into various aspects such as developing a spiral reactor for heat recovery, using software based optimization for eliminating redundant experiments analysing production cost for industrial scale-up and improving the fuel's oxidative stability by adding antioxidants for convenient long-term storage and use.